An SDRAM test education package that embeds the factory equipment into the e-learning server - José Martins Ferreira (2008)
SDRAM (Synchronous Dynamic Random Access Memory) demand has grown exponentially since the 1980s, as a result of technological factors and new areas of application, particularly concerning communication and consumer electronics. The SDRAM market represented in 2007 c. 20% of the total semiconductor business and is seen as a strategic area, justifying private and public investment in the western and far-eastern economic communities. SDRAM test education is therefore an important subject, but very high purchase and maintenance costs keep test equipment beyond reach of most university test courses. This paper presents a pilot project addressing an SDRAM test education course developed jointly by Qimonda and the University of Porto (FEUP), where the company offers remote access to one if its Advantest SDRAM automatic test equipments. Access to this remote tester was embedded into the Moodle e-learning server that supports a new course entitled Electronic Systems Testing (TSEL), which is part of the Integrated Masters degree on Electrical and Computer Engineering at FEUP. The excellent feedback received from students encouraged us to extend this cooperation into an educational network, which is also introduced in this paper.